1995
DOI: 10.1016/0092-8674(95)90412-3
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor p53 is a direct transcriptional activator of the human bax gene

Abstract: The bax gene promoter region contains four motifs with homology to consensus p53-binding sites. In cotransfection assays using p53-deficient tumor cell lines, wild-type but not mutant p53 expression plasmids transactivated a reporter gene plasmid that utilized the bax gene promoter to drive transcription of chloramphenicol acetyltransferase. In addition, wild-type p53 transactivated reporter gene constructs containing a heterologous minimal promoter and a 39-bp region from the bax gene promoter in which the p5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
467
0
3

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,861 publications
(480 citation statements)
references
References 35 publications
10
467
0
3
Order By: Relevance
“…It has been well demonstrated that p53 could mediate transcriptional activation of Bax and trigger mitochondrial apoptosis (Toshiyuki et al, 1995;Chipuk et al, 2004). Accordingly, in our study, increase of Bax expression and mitochondrial translocation was inhibited by transfecting with p53 siRNA even though p53 siRNA cannot completely knockdown the expression of p53.…”
Section: Discussionmentioning
confidence: 46%
“…It has been well demonstrated that p53 could mediate transcriptional activation of Bax and trigger mitochondrial apoptosis (Toshiyuki et al, 1995;Chipuk et al, 2004). Accordingly, in our study, increase of Bax expression and mitochondrial translocation was inhibited by transfecting with p53 siRNA even though p53 siRNA cannot completely knockdown the expression of p53.…”
Section: Discussionmentioning
confidence: 46%
“…33 After translocation to the nucleus, the phosphorylated p53 would enhance Bax gene transcription. 34 Bax translocates to the mitochondria and binds the antiapoptotic proteins Bcl-2 and Bcl-xL and inhibits their protective actions on gate-keeping, ultimately leading to mitochondrial dysfunction and activation of caspase-3. Our data on increased Bax and caspase-3 expression combined with decreased Bcl-xL expression in RPT of diabetic Tg mice lend support to this notion.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of DNA damage p53 may ac vate the ini ator caspase-2 via PIDD [1076,1077]. p53-controlled mitochondrial proteins with pro-apopto c proper es are, for example, the Bcl-2 related proteins Bax, Noxa, PUMA (p53-upregulated modulator of apoptosis) and others [1070,1078,1079].…”
Section: Endogenous Mechanism Of Ac Va On Of Apoptosismentioning
confidence: 99%